The ethical implications of the modern progress in science - Shogar, Ibrahim (IIUM Press, 2013)
Moving from the known to the unknown, creation of devices, and prophecy of the future are the distinguishing features of human species. Throughout the course of history only mankind has been able to comprehend the world and interpret its natural and historical events. On the other hand, the scientific discovery has been possible because the Creator has made the entire universe in perfect orders and precise measures. Hence, nature has been the inspiring and motivating source of knowledge. The systematic processes of nature shifted attention of man to the Creator of the universe and to the research method, since nature functions only in certain modes. The Divine originated mechanisms, such as protein and cell, have guided human talent to the discovery of new technologies. Scientists, motivated by systems in the natural world, and inspired by engines of living creatures, have shown great interest to make new discoveries. The ability to rearrange objects, therefore, lies at very foundation of systematic research and advanced technologies introduced by scientists and technologists. The main objective of modern science, as established by Francis Bacon, is to dominate nature through understanding the procedures which nature follows. This paper primarily aims to present the human ability to unfold the unknown of the natural phenomena and the ethical implications of scientific progress. The article, also, aims to introduce the Islamic epistemology as a potential philosophy of science.